Characterization and Optimization of Si-FinFET Structure Based on Gate Length and Working Temperature - Atalla, Yousif; Mamat, Mohamad Hafiz; Hashim, Yasir (International Journal of Integrated Engineering, 2025)
The ability to use a fin field effect transistor (FinFET) as a nano-temperature sensor is discussed in this research along with the transistor’s temperature sensitivity. Using the multi-gate field effect transistor (MuGFET) modeling tool, the temperature characteristics of FinFET are investigated. Once the current-voltage characteristics at different temperatures and gate lengths (Lg = 7, 10, and 20 nm) are simulated, the temperature sensitivity of FinFETs is computed considering the metal oxide semiconductor diode mode connection. The best temperature sensitivity of the FinFET is observed based on the largest ?I in the operating voltage VDD range of 0–1 V. Furthermore, between 7 and 20 nm, the FinFET’s temperature sensitivity increased linearly with channel length.